Virtual reality-based systems and their analgesic effects in the treatment of phantom limb pain: A scope review (Revista Contexto & Saúde, 2026)
Objective: To synthesize the available scientific evidence on treatment of phantom limb pain using virtual reality and its effects on pain. Method: This systematic review was conducted in accordance with the Joanna Briggs Institute (JBI) guidelines and the PRISMA-ScR (Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews) instructions. The search was conducted using five databases, as well as sources of unpublished studies and gray literature. The selection was done by two independent researchers and observed the following inclusion criteria: full-text primary articles; freely available (open-access); with no restrictions on time, language, or country; and which applied virtual reality to adult amputees with phantom pain. The results were analyzed qualitatively regarding the outcome of interest – pain – and presented descriptively in tables and graphs. Results: A total of 29 articles published between 2006 and 2024 were selected for the evidence synthesis. Most of the studies analyzed applied the concepts of mirror therapy and phantom limb movement. The immersive experience favored the use of 3D gamification. There is a tendency to assess its use in the home setting. The customized games and equipment used hamper the replication of the intervention in clinical practice. Conclusions: Although the studies under review show that virtual reality reduces phantom limb pain, their design limits the ability to determine causal relationships between virtual reality and pain reduction. Future research must employ more rigorous methodologies and larger sample sizes.
Keywords: virtual reality; virtual reality exposure therapy; phantom limb pain